Biosynthesis of silver nanoparticles using extract of Rumex nepalensis for bactericidal effect against food-borne pathogens and antioxidant activity - Geremew, Addisie; Carson, Laura; Woldesenbet, Selamawit (Frontiers in Molecular Biosciences, 2022)
The evolution and incidence of multidrug-resistant food-borne pathogens still become a critical public health global issue. To avert this challenge there is great interest in medical applications of silver nanoparticles. Thus, this study aimed to synthesize silver nanoparticles (Rn-AgNPs) using aqueous leaf extract of Nepal Dock (Rumex nepalensis Spreng) and evaluate their antibacterial potential against food-borne pathogens and antioxidant activity. The Rn-AgNPs were characterized by UV-Vis spectrophotometry, Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM), and Fourier Transform Infra-Red Spectroscopy (FTIR). The antibacterial activities of the Rn-AgNPs were evaluated using agar well diffusion (zone of inhibition, ZOI) and microdilution (minimum inhibitory concentration, MIC and minimum bactericidal concentration, MBC) methods. The antioxidant property of the Rn-AgNPs was investigated using radical scavenging (DPPH and hydroxyl) assays. The UV-Vis spectra of Rn-AgNPs elucidated the absorption maxima at 425 nm and FTIR detected numerous functional groups of biological compounds that are responsible for capping and stabilizing Rn-AgNPs. DLS analysis displayed monodispersed Rn-AgNPs of 86.7 nm size and highly negative zeta potential (-32.5mV). Overall results showed that Escherichia coli was the most sensitive organism, whereas Staphylococcus aureus was the least sensitive against Rn-AgNPs. In the antioxidant tests, the AgNPs radical scavenging activity reached 95.44% at 100 µg/mL. This study indicates that Rn-AgNPs exhibit a strong antimicrobial on L. monocytogenes, S. aureus, S. typhimurium, and E. coli and antioxidant and thus might be developed as a new type of antimicrobial agent for the treatment of multidrug-resistant foodborne pathogens and extensible applications in nanomaterial food- and nanocomposite-based antimicrobial packaging and /or as an antioxidant.